2012
DOI: 10.4236/jgis.2012.42019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Interpolation Applied a Crustal Thickness in Brazil

Abstract: The use of spatial interpolation methods of data is becoming increasingly common in geophysical analysis, for that reason, currently, several software already contain many of these methods, allowing more detailed studies. In the present work four interpolation methods are evaluated, for the crustal thickness data of Brazil tectonic provinces, with the intention of making Moho’s map of the regions. The methods used were IDW, Natural Neighbor, Spline and Kriging. We compiled 257 data that constituted a geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…given by the analysis of receiver function data compiled by Pavão et al (2012). This section clearly shows crustal thickness increasing eastward, where it reaches a depth of 44 km.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 2 more Smart Citations
“…given by the analysis of receiver function data compiled by Pavão et al (2012). This section clearly shows crustal thickness increasing eastward, where it reaches a depth of 44 km.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Regionally, the NE-SW trending zone between Amazonian and São Francisco paleoplates (Figure 1), in agreement with the main trend of TBL, is characterized by thinner lithosphere compared to adjacent terranes (Rocha et al, 2011;Azevedo et al, 2015), which may explain high intraplate seismicity along this direction (Assumpção and Sacek, 2013). Pavão et al (2012) and compiled crustal thickness values obtained with receiver-function analysis and seismic-refraction data and showed that the area of the TBL, within the northern portion of Paraná Basin, is characterized by thinned crust ranging from 31 to 36 km thick. Crust thickens southeastward toward the center of the basin, where it reaches thicknesses of between 40 and 46 km ( Figure 1).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…We built on previous compilations for South America (229 point constraints from Feng et al (2007), 244 from Lloyd et al (2010), and 183 from Tassara and Echaurren (2012), and 200 from Pavão et al (2012)) and increased the combined set of point constraints with additional data from published papers, congress proceedings, and theses, as well as unpublished monographs. We used basically two types of data: active source experiments (deep seismic refraction lines, or deep seismic reflection surveys) and receiver functions (see Fig.…”
Section: Compilation Of Crustal Thickness Datamentioning
confidence: 99%
“…A demonstração e comparação de resultados em formas de tabelas e figuras complexas têm sido a apresentação mais comum entre muitos autores (BABAK; DEUTSCH, 2009;OMRAN, 2012;PAVÃO et al, 2012). ), no caso de análise geoestatística nos trabalhos de Lima et al (2008) e Sanchez et al (2012) até análises usando a média, o desvio-padrão, a raiz quadrada do erro médio quadrático (RMSE) e o coeficiente de correlação (AMORIM et al, 2008;MCROBERTS, 2012).…”
Section: Discussionunclassified